2011
DOI: 10.5115/acb.2011.44.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol activates AMPK and suppresses LPS-induced NF-κB-dependent COX-2 activation in RAW 264.7 macrophage cells

Abstract: AMP-activated protein kinase (AMPK), an enzyme involved in energy homeostasis, regulates inflammatory responses, but its precise mechanisms are not fully understood. Recent evidence has shown that resveratrol (RES), an AMPK activator, reduces prostaglandin E2 production in lipopolysaccharide (LPS)-treated microglia. Here, we examined the effect of RES on nuclear factor kappa B (NF-κB) dependent cyclooxygenase (COX)-2 activation in LPS-treated RWA 264.7 macrophages. We found that treatment with RES increased AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Also, Steinberg et al (2006) observed that TNF-α suppresses AMPK activity by up-regulating the expression of protein phosphatase 2C, an inhibitor of AMPK signaling, thus contributing to the inflammatory process. In addition to its central mediatory function in cytokine expression, NFkB in myeloid cells may be induced by physical as well as oxidative stress of cells, or in other words via the iNOS (Carling et al, 2012;Zhang et al, 2008) or cyclooxygenase-2 (COX-2) (Yi et al, 2011). The present study found that sildenafil reduces IL-1β, TNF-α and iNOS expression.…”
Section: Discussionmentioning
confidence: 78%
“…Also, Steinberg et al (2006) observed that TNF-α suppresses AMPK activity by up-regulating the expression of protein phosphatase 2C, an inhibitor of AMPK signaling, thus contributing to the inflammatory process. In addition to its central mediatory function in cytokine expression, NFkB in myeloid cells may be induced by physical as well as oxidative stress of cells, or in other words via the iNOS (Carling et al, 2012;Zhang et al, 2008) or cyclooxygenase-2 (COX-2) (Yi et al, 2011). The present study found that sildenafil reduces IL-1β, TNF-α and iNOS expression.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have established that resveratrol can activate the AMPK pathway [31]. The activation of AMPK leads to the suppression of YAP expression [32].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, studies have found that resveratrol has a strong role in cancer prevention and treatment, and its regulatory effect can occur in various processes of tumor cell growth, division, and apoptosis . Resveratrol can play a significant role in inhibiting the progression of various cancers, including skin cancer, breast cancer, lung cancer, pancreatic cancer, and gastric cancer . In addition, the anticancer effect of resveratrol has been extensively studied at the molecular and cellular levels, such as cell signaling pathway, enzyme pathway, and p53 interface, leading to apoptosis …”
Section: Discussionmentioning
confidence: 99%